Retinol binding protein 4, obesity, and insulin resistance in adolescents - Ronaldi Noor; Eka Agustria Rini; Eti Yerizel (Indonesian Pediatric Society, 2017)
Background Obesity is a global problem. Even in poor and developing countries, obesity has reached alarming levels. In childhood, obesity may lead to insulin resistance. Retinol binding protein (RBP4), secreted primarily by liver and adipose tissues, was recently proposed as a link between obesity and insulin resistance. The role of RBP4 in pediatric obesity and its relationship with insulin resistance have not been well elucidated.Objective To compare RBP4 levels in obese and lean adolescents and to assess for a relationship between RBP4 levels and insulin resistance. Method This cross-sectional study was conducted in three senior high schools in Padang, West Sumatera, Indonesia. Subjects were adolescents aged 14-18 years, who were obese or normal weight (n=56). We measured subjectsâ€™ body mass index (BMI) and serum RBP4 concentrations. Insulin resistance was assessed using the homeostasis model assessment of insulin resistance (HOMA-IR) index.Results Similar RBP4 levels were found in the obese and normoweight groups (P>0.05). Higher RBP4 levels were found in the insulin resistant compared to the non-insulin resistant group, but the difference was not significant (P > 0.05).Conclusion There is no significant difference in mean RBP4 levels in obese adolescents compared to normoweight adolescents. Nor are mean RBP4 levels significantly different between obese adolescents with and without insulin resistance.Â Â